Rethinking the Third World: A Roundtable Discussion - Forum, The TWSC (Kasarinlan: Philippine Journal of Third World Studies, 2007)
The first 20 years of the Third World Studies Center (TWSC) creates the opportune time to reflect on the key concept that has defined the Center's institutional thrust. The Third World of the 1970s wrestled with underdevelopment, political instability and neocolonialism. Since then, its member-nations have attained different levels of economic progress and state-building. Hence, the urgent need to reassess not only the concept of "third world" but also the TWSC's orientation can no longer be ignored. The following is the transcript of the discussion held on 13 February 1997 at the CSSP Audio Visual Room, UP Diliman, Quezon City, in connection with the 20th anniversary of the TWSC.